(untitled) (Eurasian Scientific Herald, 2022)
Software has been a significant part of modern society for a long time. In particular, this paper is concerned with various software development process models. Software process model is a description of the sequence of activities carried out in a software engineering project, and the relative order of these activities. It represents some of the development models namely, waterfall, v-shaped, incremental, RAD, iterative spiral and agile model.